Disinhibition of PVN-projecting GABAergic neurons in AV region in BNST participates in visceral hypersensitivity in rats. (July 2020) - Song, Yu; Meng, Qing-Xiang; Wu, Ke; Hua, Rong; Song, Zhi-Jing; Song, Ying; Qin, Xia; Cao, Jun-Li; Zhang, Yong-Mei
Highlights: Presynaptic disinhibition contributed to the sensitization of CRH neurons in PVN to induce visceral hypersensitivity. Exogenous GABA regulated CRH neurons in PVN to mediate visceral hypersensitivity. The AV region: locale for PVN-projecting GABAergic neurons within BNST. Involvement of GABAergic neurons in AV region in visceral hypersensitivity. Optogenetic regulation of the PVN-projecting GABAergic neurons in AV region could induce the visceral behavioral changes. Abstract: Ample evidence suggests that early life stress (ELS) is a high-risk factor for the development of visceral pain disorders, whereas the mechanism underlying neuronal circuit remains elusive. Herein, we employed neonatal colorectal distension (CRD) to induce visceral hypersensitivity in rats. A combination of electrophysiology, pharmacology, behavioral test, molecular biology, chemogenetics and optogenetics confirmed that CRD in neonatal rats could predispose the elevated firing frequency of the parvocellular corticotropin-releasing hormone (CRH) neurons in the paraventricular nucleus of hypothalamus (PVN) in adulthood, with the CRH neurons activated and the frequency of spontaneous inhibitory postsynaptic currents (sIPSC) diminished, both contributing to chronic visceral hypersensitivity. Moreover, following administration of exogenous GABA (300 mM/0.5 μL) and GABAA receptor agonist muscimol (3 mM/0.5 μL) in PVN, visceral hyperalgesia was abrogated. In addition, the PVN-projecting GABAergic neurons were mainly distributed in the anterior ventral (AV) region in the bed nucleus of stria terminalis (BNST), and the excitability of these GABAergic neurons was weakened in visceral hypersensitivity. Specific depletion of the GABAergic neurons in AV region precipitated visceral hyperalgesia. Moreover, chemogenetic activation of the PVN-projecting neurons alleviated the visceral hypersensitivity. Photoactivation of PVN-projecting GABAergic neurons abated the visceral hypersensitivity in neonatal-CRD rats, whereas photoinhibition evoked visceral hyperalgesia in naïve rats. Our findings demonstrated that disinhibition of the PVN-projecting GABAergic neurons in AV region contributed to the excitation of CRH neurons, thereby mediating visceral hypersensitivity. Our study might provide a novel insight into the neuronal circuits involved in the ELS-induced visceral hypersensitivity.